Notary Role In Agricultural Land Rent Agreement In The Village Of Tungu Godong District Of Grobogan - Ani Hilyani Hilyani; Tofan Alamsyah; Aryani Witasari (Jurnal Akta, 2020)
The purpose of this research are: 1) To determine the role of the Notary in the implementation of the agreement rented farmland in the village of Tungu Godong District of Grobogan. 2) To know the rental renting Agricultural Land In the village Tungu Godong District of Grobogan. 3) To know the constraints in the implementation of the lease meyewa farmland and the solution of these constraints. The method in this research sociological juridical This study is based on positive law in Indonesia and is based on existing practices in the community. So paties directly relate to both parties, including the people who do agricultural land lease agreement.Based on the analysis of this study concluded that the role of the Notary in the lease agreement of agricultural land is the agreement made before a Notary with the deed of lease agreement, the lease which is carried out in the village Tungu done by those who do the lease agreement in line of sight crushing price to be agreed , if it is agreed the lease agreement was publishes an agreement in the agreement, such as a lease, the lease payments. The obstacles in the process of leasing such as crop failure, it is also common pests and the solution of these problems are minimized losses by means of land rent farmers cultivating land in addition to the main cropping namely rice, do matcher other crops such as corn.Keywords: Role of the Notary; Rent Agreement; Land of Agriculture.